Avaliação bacteriológica e físico-química (pH e N-BVT) da carne de Piramutaba, Brachyplatistoma vaillanti (Siluriformes, Pimelodidae) congelada comercializada em Belo Horizonte - MG. - Thiago Moreira dos Santos (2006)
The fish represents one of the most important sources of protein of animal origin for human nourishment. It has high digestibility, satisfactory levels of unsaturated fat, vitamins and minerals. Among of the animal origin products, the fish is one of the most susceptible to the spoilage process, due to intrinsic characteristics and quickly destructive action of enzymes in tissues and viscera of fish. The objective of this paper was to accomplish an inspection and make a microbiological and physic-chemical quality evaluation of Piramutaba (Brachyplatistomavaillanti) frozen, eviscerated and without head , through official methodology used by the Animal Origin Products Inspection Service of the Cattle Agriculture and Provisioning Ministry SIPA/MAPA. To do so were acquired 20 samples of the two main distributors of Belo Horizonte MG Metropolitan area. Each sample is represented by a pool of three fishes. The sensory characteristics watched were skin, eviscerated, texture, color and odor. The results do not differed statistically between the distributors (P<0,05), although the Blood and Gills were close to bedifferent. In physic-chemical tests, the Total Volatile Basic Nitrogen (TVB-N) was different and the D distributor has had the higher values although all of them were considered inside those required by law. The pH values do not differed statistically between them, but they were outside the law requirements. The microbiological analysis revealed presence of Salmonella and coagulate positive Staphylococci only in distributor A, where 10% of the samples were positive, confirming the low incidence of these pathogens in fish.